The singularity of orthographic error in the manifestations of lalangue - Calil, Eduardo; Felipeto, Cristina (Clinical Styles. The Journal on the vicissitudes of childhood, 2008)
This paper discusses the question of singularity based on orthographic errors in texts produced by children at the elementary school. We make reference to the Interactionism on language acquisition which considers, making use of Lacanian theory, the existence of a real of language and a speaker which is effect of language. This view asserts the supremacy of the signifier over the speaker, a fact Lacan insisted on. The signifiers articulate themselves through metaphorical and metonymical operators until language makes mistake.